Analisis Herding Behavior di Bursa Efek Indonesia pada Tahun 2020 - Dewi, Dinda Prasetia (E-Jurnal Akuntansi, 2023)
The aim of this study is to analyze herding behavior in the Indonesian capital market as an emerging market which has experienced high JCI volatility throughout 2020. The analysis of herding behavior takes place in three market periods: (a) throughout the 2020 period with 242 observation dates (233 after the outliers were removed), (b) ) bearish (down) conditions with 59 observation dates (51 after the outliers were removed), and (c) bullish (rising) conditions with 183 observation dates. The sample consisted of 36 companies taken from members of the LQ-45 index for the periods August 2019-January 2020, February 2020-July 2020, and August 2020-January 2021. Herding behavior was identified through regression analysis and the Cross-Sectional Absolute Deviation (CSAD) method. The results of the study did not show any herding behavior during the observation period, which means that investors make investment decisions by considering the available information. Keywords: Herding; Cross Sectional Absolute Deviation.